Collaborative Learning and New Media New Insights into an Evolving Field (Edition 1) - Ludwig, Christian; Van de Poel, Kris (Peter Lang International Academic Publishing Group, 2018)
This book is an essential resource for researchers in the field of applied linguistics as well as practising teachers and teacher trainees in secondary and higher education. It explores collaboration in the foreign language classroom through the use of new media. Combining theoretical, empirical and practical insights into this intricate area of research, the contributions take different approaches across a wide range of international contexts.